where, n = (2n + 1) is an (odd number)

So the middle terms are \( \dfrac{(n+1)}{2}\)

= \(\dfrac{ (2n+1+1)}{2}\)

=\(\dfrac{ (2n+2)}{2}\) = (n + 1) and

\( \dfrac{(n+1)}{2} + 1\)

=\(\dfrac{ (2n+1+1)}{2 + 1}\)

= (n + 1 + 1) = (n + 2)

The terms are (n + 1)^{th} and (n + 2)^{th}.

Now,

T_{n} = T_{n+1}

And,

T_{n+2} = T_{n+1+1}

Hence, the middle term is (-1)^{n}.^{2n+1}C_{n} x and (-1)^{n+1}.^{2n+1}C_{n} (\( \dfrac{1}{x}\)).

Find the term independent of x in the expansion of \( (\dfrac{3}{2x^2} – \dfrac{1}{3x})^9\)

Find the middle term in the expansion of (1 + 3x + 3x^{2} + x^{3})^{2n}

Find the middle term in the expansion of (1 – 2x + x^{2})^{n}

Find the middle term in the expansion of \( (\dfrac{x}{a} – \dfrac{a}{x})^{10}\)

Find the middle term in the expansion of \( (x^2 – \dfrac{2}{x})^{10}\)